Bentuk DanTanggungjawab Atas Terjadinya Keterlambatan Penerbangan (Delay Management) Pada Badan Usaha Angkutan Udara Niaga Berjadwal Di Indonesia - Fitriah, Fitriah (Solusi, 2017)
After the reform, in Indonesia there are many new airlines in addition to government-owned airlines. Each airline is competing to serve passengers at a low price. Airlines often offer promo tickets. With the tariff war between airlines often forget the protection of the passengers themselves. So the plane often experienced schedule delay, baggage claim lost or the worst: accident accident. To implement the provisions of Law Number 1 Year 2009 on Aviation and provide protection and service of scheduled commercial airline passengers, it is necessary to regulate Flight Delay Management at the Scheduled Commercial Air Transport Agency in Indonesia. Referring to the Law stipulated Ministerial Regulation (PM) concerning the handling of flight delays (Delay Management) at the Business Air Transport Agency Commerce Scheduled in Indonesia. In Ministerial Regulation no. 89 Year 2015 is also described the scope of flight delays and factors causing delays. The factors causing flight delays (Delay Management) at the Scheduled Air Transport Operations Agency in Indonesia (Article 5 PM 89 of 2015) are: Flight management factor, operational tennis factor, weather factor, and other factors. In the event of delayed flight, the airline is responsible for providing compensation and anti-loss to the passenger. Air transport business entities shall compensate in accordance with the category of delay as referred to in Article 3 PM 89 of 2015.